قاعدة حكم الحاكم يرفع الخلاف – دراسة تأصيلية تطبيقية - - ميلودي, علي (University of Eloued جامعة الوادي, 2017)
تناول البحث دراسة قاعدة أصولية مهمّة في أصول الفقه، ألا وهي قاعدة "حكم الحاكم يرفع الخلاف"، بحيث جمع بين الجانب التأصيلي والجانب النظري والجانب التطبيقي لها، وأقوال العلماء فيها. حيث حاول البحث الإجابة على عدّة إشكالات أهمها: التعريف بالحكم والحاكم ورفع الخلاف، والمقصود بالقاعدة، والفرق بين حكم الحاكم وفتوى المفتي. كما تناول المبحث الأخير نماذج تطبيقية عن القاعدة في كلٍّ من: العبادات، والمعاملات، والأحوال الشخصية، والنَّوازل المعاصرة. وفي الختام خُتِمَ البحث بخاتمة تناولت أهم النتائج والتوصيات المتوصل إليها. The study dealt with an important fundamental rule in the essentials of jurisprudence, which is the rule of " judgment of the Ruler raises the dispute", so that the collection of the theoretical side and the practical side, with the words of scientists Where the research used to answer several questions: the definition of the ruling and the ruler also raising the dispute, in addition to the meaning of the rule, and the difference between the ruling of the Governor and the fatwa of the Mufti The last section also dealt with applied models of the rule in: worship, transactions, personal affairs, and contemporary feature Finally, the research had been concluded with a conclusion which dealt with the most important outcomes and reached recommendations
مذكرة ماستر تخصص اصول فقه
Keywords: قاعدة، حكم، حاكم، رفع الخلاف، المفتي: judgment of ruler, dispute, contemporary, worship